Clinicopathological Profile of Glomerular Diseases: A Single Center Study (Medical Forum Monthly, 2021)
Objective: The aim to design this study was to identify and highlight the frequency and histomorphological patterns of different glomerulopathies with their clinical and laboratory profiles in tertiary care hospital.Study Design: A cross-sectional prospective studyPlace and Duration of Study: This study was conducted at Histopathology Department, Dr. Ziauddin Hospital, Karachi during the period between March 2019 to September 2019.Materials and Methods: A total of 100 renal biopsy samples with their complete relevant clinical information and other laboratory findings were included in this study. The biopsies were studied by using light and immunofluorescence microscopic techniques. The glomerular diseases were categorized as primary and secondary glomerulopathies.Results: Among total of 100 cases, there were 57% female and 43% male, mean ± SD 1.43 ± 0.498. Minimum age was 3 years and maximum was 80 years with the mean ± SD of 31.11 ± 17.506.. The most common clinical presentation was nephrotic syndrome followed by protienuria, nephritc syndrome, SLE, hematuria, oliguria and unexplained renal failure. Primary glomerulopathy was present in 82% of cases. The most common morphological picture found was FSGS (27%), followed by membranous glomerulonephritis (19%), mesangiocapillary glomerulonephritis (18%), minor changes (11%), chronic sclerosing glomerulonephritis (5%), diabetic nephropathy (5%) and amyloidosis (5%), lupus nephritis (class-I lupus nephritis, class-III lupus nephritis, class-IV & V lupus nephritis) (4%), 2 (2%) chronic sclerosing glomerulonephritis and other rare patterns.Conclusion: We conclude that primary glomerulopathy is predominant type and most common morphological pattern of glomerular disease is FSGS followed by membranous GN and mesangiocapillary glomerulonephritis with high affinity towards female.